Buying Green Without Being Seen. (April 2015) - van Dam, Ynte K.; Fischer, Arnout R. H.
Sustainable consumption is viewed as a social dilemma, in which individual rational choices lead to long-term collective harm. Construal level theory explains social dilemmas by the underlying conflict between psychologically distant and psychologically proximate goals, in which distant (sustainable) goals are relevant, but proximate goals determine actual choices. Identity theory suggests that a sustainable self-concept could increase the psychological proximity of, and thus explain, sustainable behavior. This is tested in two empirical studies in The Netherlands. The first study ( n = 229) shows that sustainable identity predicts sustainable preference, partly mediated by proximate self-confirmation motives. This mediation is moderated by sustainable identity. The second study ( n = 1, 453 households) confirms that sustainable identity directly and indirectly influences the proximate determinance of sustainable attributes, and through this determinance sustainable product choice. Jointly these studies suggest that sustainable identity explains sustainable consumption as it provides a psychologically proximate motive to act sustainably.